Avaliação da resistência de união de tubos ortodônticos submetidos a diferentes protocolos de colagem - Jardim, Alexandre Fausto da Veiga (2018)
Objective: Evaluate the shear bond strength of the union of orthodontic tubes bonded to molar teeth with different bonding protocols. Material and Method: One hundred and twenty molar teeth, previously extracted from patients with age between 12 and 30 years were selected. Orthodontic molar tubes were bonded on the vestibular surface of these teeth with one of two types of adhesive (Transbond XT or Orthobond). Each of these groups were subsequently divided in 4 other groups: control and with the use of a resin reinforcement on the occlusal surface of the bonded tubes with one of three materials (Transbond XT, Tetric N Flow, Z 350 Flow). Shear bond strength and adhesive remnant index tests were performed to evaluate the bond strength and type of fracture of the tubes bonded with the different methods. Results: Tubes bonded with Transbond XT had superior bond strength than tubes bonded with Orthobond. The use of resin reinforcement with Transbond XT increased significantly the shear bond strength of tubes bonded with Transbond XT. All groups presented in most of their samples less than 50% of adhesive remnant in the vestibular surface after de shear bond test. Conclusion: The use of a resin reinforcement with Transbond XT increased the shear bond strength of orthodontic tubes bonded with Transbond XT.